2016
DOI: 10.1210/en.2015-2029
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Pathophysiology of an Adrenal Adenoma-Associated Mutant of the Plasma Membrane Ca2+-ATPase ATP2B3

Abstract: Adrenal aldosterone-producing adenomas (APAs) are a main cause for primary aldosteronism leading to arterial hypertension. Physiologically, aldosterone production in the adrenal gland is stimulated by angiotensin II and high extracellular potassium. These stimuli lead to a depolarization of the plasma membrane and, as a consequence, an increase of intracellular Ca(2+). Mutations of the plasma membrane Ca(2+)-ATPase ATP2B3 have been found in APAs with a prevalence of 0.6%-3.1%. Here, we investigated the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 44 publications
0
39
0
1
Order By: Relevance
“…In the human adrenal gland, ATP2B1 and ATP2B3 are moderately expressed, whereas ATP2B4 shows the highest expression level, and ATP2B2 is only weakly expressed under control conditions [http://www.humanproteomemap.org, (Tauber et al . )]. Mice adrenal glands exhibit a similar expression pattern, but show the highest expression of Atp2b3.…”
Section: Atp2b3 (Plasma Membrane Ca2+‐atpase)mentioning
confidence: 96%
See 1 more Smart Citation
“…In the human adrenal gland, ATP2B1 and ATP2B3 are moderately expressed, whereas ATP2B4 shows the highest expression level, and ATP2B2 is only weakly expressed under control conditions [http://www.humanproteomemap.org, (Tauber et al . )]. Mice adrenal glands exhibit a similar expression pattern, but show the highest expression of Atp2b3.…”
Section: Atp2b3 (Plasma Membrane Ca2+‐atpase)mentioning
confidence: 96%
“…, Tauber et al . ). With respect to their role in Ca 2+ extrusion and their high adrenal expression level, there is no doubt about an important function of PMCAs for the Ca 2+ signalling in glomerulosa cells.…”
Section: Atp2b3 (Plasma Membrane Ca2+‐atpase)mentioning
confidence: 97%
“…Clinically APAs containing ATP2B3 mutations are associated with higher levels of aldosterone secretion when compared with wild-type APAs (27,186,397), most likely as a result of an observed increase in aldosterone synthase CYP11B2 expression (250,254,396). Recently these associations have been confirmed through the transfection of ATP2B3 carrying the common Leu425_Val426 deletion into adrenocortical NCI-H295R cells, resulting in impaired Ca 2ϩ clearance accompanied by elevated basal Ca 2ϩ , CYP11B2 expression, and aldosterone secretion (370). This highlights a highly specialized function for this isoform in nonneuronal tissue.…”
Section: Pmca3 Cerebellar Ataxia and Adenomamentioning
confidence: 96%
“…All the mutations identified in ATP2B3 are located in the M4 domain, deletions of at least two amino acids in a specific region between amino acids 425 and 433 , Dutta et al 2014, FernandesRosa et al 2014, Akerstrom et al 2015, Scholl et al 2015a, Zheng et al 2015, a region crucial for the binding of Ca 2+ ions but also close to the catalytic core of the pump (Di Leva et al 2008). Electrophysiological studies have shown that the ATP2B3 p.Leu425_Val426del mutation leads to increased intracellular Ca 2+ concentration in transfected human embryonic kidney (HEK-293) cells due to an increased Ca 2+ influx and reduced capacity to export Ca 2+ , suggesting a loss of the physiological pump function (Tauber et al 2016). In addition to the alteration of Ca 2+ equilibrium, ATP2B3 mutations, like KCNJ5 but to a less extent, lead to Na + and possibly Ca 2+ influx into the cells, contributing to increased intracellular Ca 2+ concentration also through depolarization of the cell membrane and opening of voltage-gated Ca 2+ channel.…”
Section: R51 Review F L Fernandes-rosa S Boulkroun and Othersmentioning
confidence: 99%
“…In addition to the alteration of Ca 2+ equilibrium, ATP2B3 mutations, like KCNJ5 but to a less extent, lead to Na + and possibly Ca 2+ influx into the cells, contributing to increased intracellular Ca 2+ concentration also through depolarization of the cell membrane and opening of voltage-gated Ca 2+ channel. These alterations are associated to increased aldosterone production and CYP11B2 expression in adrenocortical cells (Tauber et al 2016).…”
Section: R51 Review F L Fernandes-rosa S Boulkroun and Othersmentioning
confidence: 99%